2018
DOI: 10.1080/00343404.2018.1500687
|View full text |Cite
|
Sign up to set email alerts
|

Multilevel policy governance and territorial adaptability: evidence from Japanese SME innovation programmes

Abstract: Science, Technology and Innovation policies increasingly operate in a multilevel policy governance structure. This paper analyses the variety of local authorities' innovation support mechanisms for small and medium enterprises (SMEs) in Japan, drawing on a unique dataset of 241 local SME R&D subsidy programmes at the prefecture and city/municipality levels. The variation of SME R&D subsidy programmes in terms of institutional forms and coordination practices of multilevel innovation support mechanisms is analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 35 publications
(48 reference statements)
0
15
0
1
Order By: Relevance
“…In the Japanese context, growing roles are recognized for municipalities (i.e. cities and towns) rather than at the prefectural level (Okamuro et al., 2019). Large metropolitan cities and smaller towns and places need to collaborate more to create and build larger ecosystems and enhance cross/inter-sectoral collaboration.…”
Section: Policy Diversitymentioning
confidence: 99%
“…In the Japanese context, growing roles are recognized for municipalities (i.e. cities and towns) rather than at the prefectural level (Okamuro et al., 2019). Large metropolitan cities and smaller towns and places need to collaborate more to create and build larger ecosystems and enhance cross/inter-sectoral collaboration.…”
Section: Policy Diversitymentioning
confidence: 99%
“…Okamuro and Nishimura (2018b) found that, as of 2015, at least 131 cities among around 800 cities in Japan have already implemented their own R&D subsidy programs for local SMEs with different program designs according to different local needs and conditions. Okamuro et al (2019) discuss the multilevel governance of public R&D support in Japan with original survey data and some case studies, and they show some distinct differences in subsidy schemes between prefecture and city level programs.…”
Section: Policy Overviewmentioning
confidence: 99%
“…Not only the national government, but regional governments and local authorities, including state, prefecture, and city levels, are responsible for the development of local firms and innovation systems (Fernandez-Ribas 2009;Okamuro et al 2019). Nonetheless, there is not sufficient empirical evidence on the relationship between the central and local governments in the discussion of regional innovation systems.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations